Comparison between oral procainamide and mexiletine for the treatment of recurrent and refractory ventricular tachyarrhythmias. (19th May 2022) - Toniolo, M; Burelli, M; Mugnai, G; Rebellato, L; Daleffe, E; Bilato, C; Muser, D
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: The antiarrhythmic therapy of recurrent ventricular arrhythmias in patients having undergone catheter ablation and in whom amiodarone and/or beta blockers were ineffective or contraindicated, is a controversial issue. Purpose: The present study sought to compare the efficacy and tolerability of oral procainamide and mexiletine in patients with recurrent ventricular arrhythmias, when the standard therapy strategy failed. Methods: All patients with an implantable cardioverter defibrillator (ICD) treated with oral procainamide or mexiletine for recurrent ventricular tachycardia (VT) or ventricular fibrillation (VF) in 2 Cardiology Divisions between January 2010 and January 2020 were enrolled. The patients were divided in group A (oral procainamide) and group B (mexiletine) and the 2 groups were compared to each other. The primary endpoint was the efficacy of therapy; the secondary endpoint was the discontinuation of therapy. All the events occurring during procainamide or mexiletine treatment were compared with a matched duration period before the initiation of the therapy. Antiarrhythmic therapy was considered effective when an ≥80% reduction of the sustained ventricular arrhythmias (SVA) burden recorded by the ICD was achieved. Results: A total of 68 consecutive patients (61 males, 89.7%; mean age 74 ± 10 years) were included in this retrospective analysis. In 27 (39.7%) patients catheter ablation of VT was attempted before therapy initiation. A concomitant therapy with amiodarone was present in 25 (36.8%) patients. The mean dose of procainamide was 1207±487 mg/die. The mean dose of mexiletine was 576±66 mg/die. After a median follow-up of 19 months, 38 (56%) patients had a significant reduction in the SVA burden. After multivariable adjustment (Table 1), therapy with procainamide was independently associated with an almost 3-fold higher efficacy on VA suppression compared to mexiletine (HR 2.54, 95% CI 1.06-6.14, p=0.03). Similar results (HR 2.89, 95% CI 1.26-6.62, p=0.01) were found after adjustment using inverse probability weighting by a propensity score including age, gender, left ventricular ejection fraction, ischemic heart disease and concomitant amiodarone therapy. Only 3 patients (9%) treated with procainamide presented severe side effects (dyspnea or hypotension) requiring discontinuation of therapy against 6 patients (18%) treated with mexiletine who interrupted therapy because of severe side effects (p=0.47). Conclusions: Compared to mexiletine, oral procainamide has a higher efficacy for the treatment of recurrent and refractory VAs and shows a good profile of tolerability Table 1. Multivariable Cox Proportional Hazards Analysis of Baseline Covariates in Relation to effective VAs suppression.